Epigenetic modifiers can alter telomerase expression and clonogenic capacities of Sézary cells. (October 2021) - Chebly, Alain; Prochazkova-Carlotti, Martina; Idrissi, Yamina; Bresson-Bepoldin, Laurence; Poglio, Sandrine; Pham-Ledard, Anne; Beylot-Barry, Marie; Merlio, Jean Philippe; Chevret, Edith
Abstract : Sézary syndrome (SS) is an aggressive leukemic variant of cutaneous T-cell lymphomas (CTCL) for which current available treatments do not provide long-term responses. Two epigenetic-modulating agents belonging to the family of histone deacetylase inhibitors (HDACi), vorinostat and romidepsin are FDA approved for advanced stage CTCL. However, the rationale for using such therapies in SS and their biological impact are not well defined. The majority of cancer cells achieve proliferative immortality by activating or upregulating the normally silent human Telomerase Reverse Transcriptase ( hTERT ) gene. Sezary cells do not escape to this phenomenon. As the hTERT promoter is rich in CpG, we investigated the contribution of epigenetic mechanisms in its re-expression. We analyzed hTERT -promoter methylation status in CTCL cells compared to healthy cells. Nine CTCL cell lines including, five SS cell lines were experimentally investigated (HuT78, the unique commercial SS cell line and four newly developed SS cell lines from our laboratory (PMID: 33106625). Gene-specific methylation analyses revealed a common promotor hypermethylation pattern exclusively observed in tumor cells. We explored hTERT promoter methylation status under the pressure of a demethylating agent approved for the treatment of several hematological disorders (5-azacytidine) by comparison with clinically approved HDACi (romidespin and vorinostat). Surprisingly, romidespin, vorinostat or 5-azacytidine could each reduce hTERT expression level without altering the methylation status of hTERT promoter. To go further, we analyzed the functional effect of the aforementioned epidrugs on the clonogenic capacities of Sézary cells using the soft agar assay. Our data revealed that, besides hTERT downregulation, epidrugs reduced the proliferative and the tumor formation capacities in Sézary cells in vitro . Our first report on hTERT promotor methylation status in CTCL suggests that hTERT promotor methylation status is a hallmark of neoplastic CTCL cells. Our results also provide evidence for functional consequences of epidrugs treatments on tumor formation capacities in Sézary cells in vitro . Indeed, the present investigation states that Sézary cells' clonogenic capacity correlates well with hTERT expression level under epigenetic drugs pressure. The present findings represent a step forward towards a better understanding of the relationship between targeting epigenetic modifiers in a cell-context–dependent manner and the response generated at the cellular levels.